2021
DOI: 10.1177/03080226211009419
|View full text |Cite
|
Sign up to set email alerts
|

Occupations creating joy for people living with advanced cancer: A qualitative descriptive study

Abstract: Introduction For people living with advanced cancer, the possibilities for experiences of joy are seriously influenced by the consequences of the illness. Due to the limited expected lifetime, the need to support such experiences that may entail joy and contribute to quality of life are of importance. Research shows that people with advanced cancer experience quality of life through occupations they are able to perform and enjoy. The aim of this study was to describe which occupations contribute to joy for peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…The authors interpreted that the group's speeches are in line with the researched occupational therapy literature regarding leisure, since it also reinforces the presence of pleasure as a substantial element in leisure (Alcântara & Brito, 2012;Alegría et al, 2013;Almeida et al, 2018;Costa, 2008;Queiroz, 2020). The same can be said in the stronghold of occupational science, since feelings involving pleasure -such as joy, happiness and satisfaction -are present in the literature that addresses leisure (Atler et al, 2016;Bentz et al, 2022).…”
Section: (A) Leisure -Pleasurementioning
confidence: 80%
“…The authors interpreted that the group's speeches are in line with the researched occupational therapy literature regarding leisure, since it also reinforces the presence of pleasure as a substantial element in leisure (Alcântara & Brito, 2012;Alegría et al, 2013;Almeida et al, 2018;Costa, 2008;Queiroz, 2020). The same can be said in the stronghold of occupational science, since feelings involving pleasure -such as joy, happiness and satisfaction -are present in the literature that addresses leisure (Atler et al, 2016;Bentz et al, 2022).…”
Section: (A) Leisure -Pleasurementioning
confidence: 80%
“…Os autores interpretaram que as falas do grupo estão em alinhamento com a literatura da terapia ocupacional pesquisada no tocante ao lazer, visto que ela também reforça a presença do prazer como elemento substancial no lazer (Alcântara & Brito, 2012;Alegría et al, 2013;Almeida et al, 2018;Costa, 2008;Queiroz, 2020). O mesmo pode ser dito no reduto da ciência ocupacional, uma vez que sentimentos que envolvem o prazer -como alegria, felicidade e satisfação -estão presentes na literatura que aborda o lazer (Atler et al, 2016;Bentz et al, 2022).…”
Section: (A) Lazer -Prazerunclassified
“…The study also found that nearly all participants had difficulties engaging in everyday activities that they regarded as important, for example, hobbies and craft, gardening, walking, cycling and household activities (Wæhrens et al, 2019). Continued engagement in everyday activities is important for people with advanced cancer at the end of life and may ease suffering (Bentz et al, 2021; Svidén et al, 2010; von Post & Wagman, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…in everyday activities is important for people with advanced cancer at the end of life and may ease suffering (Bentz et al, 2021;Svidén et al, 2010;von Post & Wagman, 2019).…”
mentioning
confidence: 99%